Proficiency_]testing scheme for essential oils - Messineo, E.; Varfi, A.; Minziere, J.; Boubetra, A.
BIPEA (http://www.bipea.org)organizes regular proficiency?testing schemes (PTS)in many analytical domains, including the analysis of essential oils. As an example, in September and October 2015, two tests were conducted using essential pine oil, with respectively 27 and 32 participating laboratories. The first test was intended for routine quality?control analyses (density, refractive index optical rotation, flash?point, peroxide value, and acid value), whereas the second was intended for the analysis of the composition of this essential oil, by determination of its profile by gas chromatography with flame?ionization detection (for 22 constituents of this particular essential oil). Participating laboratories were required to return their results on a dedicated website within a period of 1 month, and a statistical treatment of the data was as usually performed by BIPEA according to ISO 13528.p1(B. Assigned (consensus)values were calculated from the participants' results, and the performances of the laboratories could then be evaluated individually and collectively according to ISO 17043. p2 (BThese tests allow participating laboratories to draw up a general inventory of their analytical skills, and are a very useful tool to detect bias or non?compliant results; they act as a warning signal for the implementation of corrective and/or curative actions in the laboratory.s
Keywords: ESSENTIAL OILS; GC-FID PROFILE; LABORATORY PERFORMANCE; PROFICIENCY?TESTING SCHEMES; QUALITY CONTROL